Relationship between high-risk human papilloma virus (HPV) and subclinical condyloma acuminata (CA) in the cervix of high-risk women - Benjamin Ricardo Rubirosa Lumban Tobing; Richard Hutapea; Kristina Nadeak (Universitas Gadjah Mada, 2022)
Condyloma acuminata (CA) is a sexually transmitted infection (STI) caused by both high- and low risk human papilloma virus (HPV) infection. Subclinical CA looks like a white spot after an acetic acid test. High-risk women are women who have a high risk of STIs, including CA. The aim of this study was to evaluate the relationship between high-risk HPV and subclinical CA in the cervix of high-risk women. This was a cross-sectional analytic study involving 30 high-risk women. The age, the age at first sexual intercourse, the frequency of sexual intercourse, the number of sexual partners and the use of condoms were recorded. Subclinical CA was diagnosed by the 5% acetowhite test. HPV infection was detected by PCR. Kruskal Wallis test was conducted to evaluate the relationship between variables and the results were considered to be significant if p<0.05. The HPV infection was detected in 15 high-risk women with subclinical CA and most subjects showed the high-risk type. No significantly relationship between age and using of condom with high-risk HPV or with subclinical CA (p> 0.05). No significantly relationship between age at first sexual intercourse and frequency of sexual intercourse with high-risk HPV was also observed (p> 0.05), however, a significantly relationship with subclinical CA was observed (p < 0.05). In conclusion, there is a relationship between high-risk HPV and subclinical CA in the cervix of high-risk women.